Correlation Analysis of Stock Price Movements between Large State- owned Listed Enterprises and Small-Medium Size Listed Companies : Based on Data Analysis of Share Listed Companies Since 2020 - Lu, Wendian; Deng, Guirong (PT Larva Wijaya Penerbit, 2025)
This study investigates the correlation in stock price movements between large state-owned listed enterprises (SOEs) and small to medium-sized listed companies (SMEs) in the context of China's capital market since 2020. Utilizing quantitative data analysis methods, including Pearson correlation coefficients and time-series analysis, the research analyzes the daily stock price data of a representative sample of both SOEs and SMEs. The findings reveal a moderate to low correlation between the two groups, suggesting distinct market behavior and sensitivity to macroeconomic factors, policy changes, and investor sentiment. Large SOEs tend to show more stability and policy-driven price movement, whereas SMEs exhibit higher volatility and stronger reactions to market dynamics. This differentiation highlights the importance of portfolio diversification and sectoral analysis for investors aiming to optimize risk-adjusted returns. The study contributes to a deeper understanding of market segmentation and inter-firm dynamics within emerging economies.